2009
DOI: 10.1136/jnnp.2008.150011
|View full text |Cite
|
Sign up to set email alerts
|

Camptocormia in Parkinson disease: an epidemiological and clinical study

Abstract: Camptocormia, a relatively common sign in PD seems to be related to the clinical severity of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(128 citation statements)
references
References 22 publications
8
109
1
10
Order By: Relevance
“…Camptocormia is an abnormal posture with marked flexion of the thoracolumbar spine, and it increases with time and fatigue during the day and during walking; it is a progressive postural insufficiency that abates in recumbent position, sitting or volitionally when the PD patient leans against a wall. There are usually no radiographic abnormalities or structural changes referring to that kind of neuromuscular dysfunction [1,12,24,32,39]. Camptocormia in PD patients was observed with an incidence of 7% dependant on the clinical severity of the PD.…”
Section: Discussionmentioning
confidence: 99%
“…Camptocormia is an abnormal posture with marked flexion of the thoracolumbar spine, and it increases with time and fatigue during the day and during walking; it is a progressive postural insufficiency that abates in recumbent position, sitting or volitionally when the PD patient leans against a wall. There are usually no radiographic abnormalities or structural changes referring to that kind of neuromuscular dysfunction [1,12,24,32,39]. Camptocormia in PD patients was observed with an incidence of 7% dependant on the clinical severity of the PD.…”
Section: Discussionmentioning
confidence: 99%
“…In a single-center epidemiological study on 275 consecutive outpatients with Parkinson’s disease, the prevalence of camptocormia was 6.9% [15]. The occurrence of camptocormia in this study was related to the severity of Parkinson’s disease [15]. …”
Section: Frequencymentioning
confidence: 99%
“…The reported prevalence varies widely. Tiple et al [15] revealed a prevalence of 6.9% in their outpatients (19/275). In contrast, Lepoutre et al [16] gave a hypothetic prevalence of 3% (23/700), but there are no prospective epidemiological studies as yet.…”
Section: Introductionmentioning
confidence: 99%